Rethinking teaching and teachers: Bringing content back into conversation (UCL Press, 2018)
The question of content - that is, knowledge in the curriculum - has all but disappeared from global policy and academic discourses concerning teaching and teachers. Invoking the work of Michael Young and his colleagues concerning 'bringing knowledge back in', Bildung-centred Didaktik, and Joseph J. Schwab's curriculum thinking, this article attempts to bring content back into the conversation on teaching and teachers. The discussion yields an educational, curricular understanding of teaching and teachers by making three arguments. First, teaching (content) is an 'intergenerational' task vital for social reproduction and innovation. Second, teaching, by way of a meaningful encounter between content and students, contributes to their self-formation and the development of human powers and dispositions. Third, teaching is a practical, interpretive act that calls for curriculum thinking that is centred on the 'what' (content) and 'why' (purpose) of teaching.